2010
DOI: 10.1159/000320134
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injuries without Radiographic Abnormality at Two Pediatric Trauma Centers in Ontario

Abstract: Background: Spinal cord injury without radiographic abnormality (SCIWORA) represents a traumatic myelopathy, either transient or permanent, that is not associated with visible vertebral fractures or ligamentous abnormalities on plain radiographs or CT. MRI has become essential in the diagnosis and evaluation of trauma patients and in predicting the long-term neurological outcome. Methods: The medical charts of 578 children with vertebral trauma at the Children’s Hospital of Eastern Ontario and the Hospital for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 76 publications
0
18
0
2
Order By: Relevance
“…19 We identified 2 (6%) cases of SCIWORA in the patients with myelopathic changes (n = 34), which is within the wide range of published estimates of SCIWORA in the pediatric population with reported ranges of 1.3%-38%. 5,8,11,20 The positive MRI results of these 2 patients assisted in the identification and prognosis of their injuries.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…19 We identified 2 (6%) cases of SCIWORA in the patients with myelopathic changes (n = 34), which is within the wide range of published estimates of SCIWORA in the pediatric population with reported ranges of 1.3%-38%. 5,8,11,20 The positive MRI results of these 2 patients assisted in the identification and prognosis of their injuries.…”
Section: Discussionmentioning
confidence: 97%
“…Trigylidas and colleagues 20 found that 10% of myelopathic patients presented with associated head injuries and that 50% of these head injuries occurred in patients with SCIWORA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have proportionately bigger skulls matched by their bodies and have immature cervical musculature (22). They similarly have innate ligamentous laxity, elasticity, and imperfect ossification (23).…”
Section: Biomechanical Possessionsmentioning
confidence: 99%
“…Spinal cord injury without radiological abnormality (SCIWORA) is a specific entity, which has been described since the early 1980s, and its estimated incidence in children ranges between 19 and 34% [1]. Its pathophysiological mechanism derives directly from the specific anatomical features of the paediatric spine [2,3,4]. The spinal lesions are caused by longitudinal distraction and ischaemia [4].…”
Section: Introductionmentioning
confidence: 99%